Epidemiologic evaluation and management of patients with orbital fractures admitted to plastic and reconstructive surgery ward in Imam Khomeini hospital, Tehran, Iran - Ezzatollah Rezaei; Mohammad Reza Farevash; Mahdi Fathi (Iranian Journal of Otorhinolaryngology, 2009)
Introduction: Orbital fractures comprise a significant part of facial traumas. The purpose of this study was to evaluate the outcome and epidemiologic features of patients with orbital fractures in Imam Khomeini hospital over a 10-year period. Materials and Methods: One hundred and three patients with orbital fractures were included in this study. Data obtained from medical records of patients were statistically analyzed. Results: 68% of patients were in the age range of 20-40. The male to female ratio was 5 to 1. Motor vehicle accidents were the main cause of injury and most frequently involved area was the orbital floor. The main clinical finding was echymosis and the most common associated injury was zygomatic bone fracture. Diplopia, enophthalmos and deformity were improved in 94.5%, 86.2% and 87.5% of cases postoperevtively. The frequency of enophthalmos in patients with medial wall fracture was significantly more than patients with fractures of other orbital areas (P